Tectonic inversion of listric normal faults in the foreland of the Rinkian Orogen (Maarmorilik, central West Greenland). (June 2022) - Guarnieri, Pierpaolo; Baker, Nigel
Abstract: Integration of field structural data and 3D-photogeology from the southern part of the Rinkian Orogen, in central West Greenland, indicates that Paleoproterozoic marbles of the Mârmorilik Formation were deformed by two compressional events in the foreland of the orogen, associated with tectonic inversion of normal faults. Tectonic transport and folding post-date the Rinkian metamorphism (c. 1830–1800 Ma) with the first event characterized by NNE-SSW oriented compression and tectonic stacking of folded calcitic marbles (Black Angel Tectonic Unit), above slightly deformed dolomitic marbles (South Lakes Tectonic Unit). The second event caused the inversion of NE-SW trending normal faults during NW-SE oriented compression. Field observations reveal that the normal faults have a listric geometry and were inverted after c. 20° tilting to the NE of the Maarmorilik carbonate platform. The style of tectonic inversion reflects the amount of extension accommodated along the listric faults showing rollover anticlines and extensional fault-bend-folds in the hanging wall, then inverted as thrust anticlines, back-thrusts antithetic to the normal fault or normal faults passively truncated by younger thrusts. This paper shows the power of 3D-photogeology that can provide observations of lithostratigraphic units and structural data to allow investigation of remote areas from otherwise inaccessible outcrops. Highlights: Tectonic inversion in the foreland of the Rinkian Orogen. Normal listric faults inverted during thick-skinned tectonics. 3D-photogeology, a powerful tool to investigate remote and inaccessible areas. Paleoproterozoic deformation in central West Greenland.